Consilience : the unity of knowledge - Wilson, Edward O., 1929- (New York : Knopf : Distributed by Random House, 1998)
Examines the fundamental unity of all knowledge and the need to search for consilience--the proof that everything in our world is organized in terms of a small number of natural laws that comprises all learning.
The Ionian enchantment -- The great branches of learning -- The Enlightenment -- The natural sciences -- Ariadne's thread -- The mind -- From genes to culture -- The fitness of human nature -- The social sciences -- The arts and their interpretation -- Ethics and religion --To what end?
'A Borzoi book.'
Includes bibliographical references (p. 299-319) and index.
HU OSA 385 - Donation of Victor M. Fic
Keywords: Philosophy; Order (Philosophy); Philosophy and science